The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12936-016-1535-8
|View full text |Cite
|
Sign up to set email alerts
|

Failure of dihydroartemisinin plus piperaquine treatment of falciparum malaria by under-dosing in an overweight patient

Abstract: BackgroundArtemisinin-based combination therapy (ACT) introduced in the mid-1990s has been recommended since 2005 by the World Health Organization as first-line treatment against Plasmodium falciparum in all endemic countries. In 2010, the combination dihydroartemisinin–piperaquine (DP) was recommended for the treatment of uncomplicated P. falciparum malaria. DP is one of the first-line treatments used by the French army since 2013.Case presentationA case of P. falciparum clinical failure with DP at day 20 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In Vietnam, before 2016, DHA-PPQ treatment dose depended on patient’s age [ 50 ]. However, many studies have showed that PPQ under-dosing (< 48 mg/kg) is an important factor for recrudescent parasitaemia [ 48 , 51 ]. It is documented that the underdose of DHA-PPQ increases recrudescent parasitaemia and sequentially increases treatment failure [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, before 2016, DHA-PPQ treatment dose depended on patient’s age [ 50 ]. However, many studies have showed that PPQ under-dosing (< 48 mg/kg) is an important factor for recrudescent parasitaemia [ 48 , 51 ]. It is documented that the underdose of DHA-PPQ increases recrudescent parasitaemia and sequentially increases treatment failure [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, before 2015 DHA-PPQ treatment dose depended on patient's age (46). However, many studies have showed that PPQ underdosing (<48mg/kg) is an important factor for recrudescent parasitemia (44,47). In order to optimize the effectiveness of DHA-PPQ, the WHO recommends treatment with 3 days of ATCs to cover at least two asexual life circles of P. falciparum and DHA-PPQ weight-based dosing (7).…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, before 2016, DHA-PPQ treatment dose depended on patient's age (54). However, many studies have showed that PPQ under-dosing (< 48 mg/kg) is an important factor for recrudescent parasitemia (52,55). It is documented that the underdose of DHA-PPQ increases recrudescent parasitemia and sequentially increases treatment failure (52).…”
Section: Demographic Characteristics Of Study Participantsmentioning
confidence: 99%